Role of murine integrin α2β1 in thrombus stabilization and embolization: Contribution of thromboxane A2 - Kuijpers, Marijke J. E.; Pozgajova, Miroslava; Cosemans, Judith M. E. M.; Munnix, Imke C. A.; Eckes, Beate; Nieswandt, Bernhard; Heemskerk, Johan W. M. (Thrombosis and Haemostasis, 2007)
Platelets stably interact with collagen via glycoprotein (GP)VI and α2β1 integrin. With α2-null mice, we investigated the role of α2β1 in thrombus formation and stability in vivo and in vitro. Using a FeCl3-induced thrombosis model, in arteries from α2-null mice smaller thrombi were formed with more embolization compared to vessels from wild-type mice. Aspirin treatment of wild-type mice causes similar effects, while the thromboxane A2 analogue U46619 was borderline effective in suppressing the embolisation in α2-null mice. In vitro, perfusion of α2-null blood over collagen resulted in formation of thrombi that were smaller and looser in appearance, regardless of the presence or absence of coagulation. Aspirin treatment or blockage of thromboxane receptors provoked embolus formation in wildtype blood, while U46619 normalized thrombus formation in blood from α2-null mice. We conclude that integrin α2β1 plays a role in stabilizing murine thrombi, likely by enhancing GPVI activation and thromboxane A2 release. The increased embolization in α2-null mice may argue against the use of α2β1 integrin inhibitors for antithrombotic therapy.
Keywords: Collagen receptors; integrins; mice; platelets; thrombus